2003
DOI: 10.1242/jeb.00376
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and serotonin-induced activation of vacuolar-type H+-ATPase in the salivary glands of the blowflyCalliphora vicina

Abstract: SUMMARYSecretory activity in blowfly salivary glands is activated by the hormone serotonin. We have investigated the distribution and activity of two cation pumps that are possibly involved with transepithelial ion transport, i.e. Na+/K+-ATPase and vacuolar-type H+-ATPase(V-ATPase). By immunofluorescence labelling of secretory cells,Na+/K+-ATPase was localized on the basolateral plasma membrane and V-ATPase on the highly folded apical membrane. Activities of both ATPases were probed in salivary gland homogenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 55 publications
4
59
0
Order By: Relevance
“…Cross-reactivity of these antibodies with the homologous proteins in C. vicina has been demonstrated previously (Zimmermann et al, 2003;Dames et al, 2006;Voss et al, 2007;Voss et al, 2009;Baumann and Walz, 2012). Monoclonal anti-actin (clone C4) was obtained from Merck (Darmstadt, Germany), rabbit antiserum (cat.…”
Section: Reagentsmentioning
confidence: 93%
See 2 more Smart Citations
“…Cross-reactivity of these antibodies with the homologous proteins in C. vicina has been demonstrated previously (Zimmermann et al, 2003;Dames et al, 2006;Voss et al, 2007;Voss et al, 2009;Baumann and Walz, 2012). Monoclonal anti-actin (clone C4) was obtained from Merck (Darmstadt, Germany), rabbit antiserum (cat.…”
Section: Reagentsmentioning
confidence: 93%
“…To determine the structural reorganization of the apical membrane domain during cell differentiation, cryosections through salivary glands at various developmental stages were labelled with fluorophore-tagged phalloidin. Since microplicae have actin filaments in their interior, staining with the F-actin probe phalloidin visualizes the entire apical membrane of fully differentiated secretory cells in the adult salivary gland (Zimmermann, 2000;Zimmermann et al, 2003;Rotte et al, 2008).…”
Section: Structural Differentiation Of the Apical Plasma Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the serotonininduced increase in cyclic AMP (cAMP) activates an electrogenic K + transport mechanism (Berridge et al, 1976) that today is thought to derive from the V-type H + ATPase working in parallel with a K + /H + antiporter (Wieczorek et al, 1999). Immunofluorescent labeling of different V-ATPase subunits, as well as measurements of enzyme activity, have shown that serotonin recruits V 1 subunits from the cytosol, consistent with the assembly of the V 1 V 0 holoenzyme (Zimmermann et al, 2003). In Malpighian tubules of insects, where intracellular second messengers of diuresis and antidiuresis have been identified, it remains unknown whether cAMP, cGMP, Ca 2+ and NO affect the disassembly/reassembly of the V 1 V 0 holoenzyme.…”
Section: Regulation Of the V-type H + Atpasementioning
confidence: 99%
“…A vacuolar H + -ATPase (V-ATPase) located in the apical membrane of the gland cells is of fundamental importance for fluid secretion. Active VATPase generates an inward-directed electrochemical H + -gradient that is used by a putative nH + /K + antiporter for K + transport into the glandular lumen (Dames et al, 2006;Rein et al, 2008;Wieczorek et al, 1991;Zimmermann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%